A generalization of the Itô formula - Said Ngobi (International Journal of Mathematics and Mathematical Sciences)
The classical Itô formula is generalized to some anticipating processes. The processes we consider are in a Sobolev space which is a subset of the space of square integrable functions over a white noise space. The proof of the result uses white noise techniques.